2010
DOI: 10.1111/j.1442-9071.2010.02289.x
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation syndrome related to sensorineural hearing loss

Abstract: The above results are in accordance with previous studies and provide additional evidence of the association between exfoliation syndrome and sensorineural hearing loss at high frequencies. Particular effect was shown on the highest frequency of 8 kHz. These findings may support the systemic nature of exfoliation syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
0
31
0
1
Order By: Relevance
“…Papadopoulos et al also pointed out an association between PEX and hearing impairment, but in the high frequency ranges, particularly 8 kHz [21,22]. In objective hearing tests like DPOAE and ABR, Paliobei et al found that patients with PEX showed a greater prevalence of retrocochlear pathology [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Papadopoulos et al also pointed out an association between PEX and hearing impairment, but in the high frequency ranges, particularly 8 kHz [21,22]. In objective hearing tests like DPOAE and ABR, Paliobei et al found that patients with PEX showed a greater prevalence of retrocochlear pathology [23].…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the stiffening of the vibrating basilar membrane of the cochlea is most noticeable for this particular frequency. Another theory is that deposits in vessel walls lead to an impaired blood supply to the inner ear [21]. This hypothesis is justified by the fact that the hair cells responsible for the perception of stimuli in high frequency ranges are the most sensitive to ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies exploring PXF and hearing loss generally support a relationship, but it is not clear whether it is more common in PXF alone or in conjunction with PXF glaucoma 58–62,68–70 . In addition, there is no consensus on whether the hearing loss is generalized or specific to select octave bands.…”
Section: Auditory Systemmentioning
confidence: 99%
“…[64][65][66][67] Studies exploring PXF and hearing loss generally support a relationship, but it is not clear whether it is more common in PXF alone or in conjunction with PXF glaucoma. [58][59][60][61][62][68][69][70] In addition, there is no consensus on whether the hearing loss is generalized or specific to select octave bands. Turacli et al (2007) revealed a higher incidence of hearing loss in individuals with PXF compared with those without PXF.…”
Section: Auditory Systemmentioning
confidence: 99%
“…; Papadopoulos et al. , ; Paliobei et al. ); yet, most of these studies were not performed in conjunction with otologists, nor do they provide any otopathological correlation.…”
Section: Introductionmentioning
confidence: 99%